Phase Retrieval of One-Dimensional Objects by the Multiple-Plane Gerchberg–Saxton Algorithm Implemented into a Digital Signal Processor - Karitans, Varis; Ozolinsh, Maris; Fomins, Sergejs (MDPI, 2024)
In the current study, we address the phase retrieval of one-dimensional phase objects from near-field diffraction patterns using the multiple-plane Gerchberg–Saxton algorithm, which is still widely used for phase retrieval. The algorithm was implemented in a low-cost digital signal processor capable of fast Fourier transform using Q15 arithmetic, which is used by the previously mentioned algorithm. We demonstrate similarity between one-dimensional phase objects, i.e., vectors cut out of a phase map of the tertiary spherical aberration retrieved by the multiple-plane Gerchberg–Saxton algorithm, and these vectors are measured with a non-contact profiler. The tertiary spherical aberration was induced by a phase plate fabricated using grayscale lithography. After subtracting the vectors retrieved by the algorithm from those measured with the profiler, the root mean square error decreased, while a corresponding increase in the Strehl ratio was observed. A single vector of size 64 pixels was retrieved in about 2 min. The results suggest that digital signal processors that are capable of one-dimensional FFT and fixed-point arithmetic in Q15 format can successfully retrieve the phase of one-dimensional objects, and they can be used for applications that do not require real-time operation, i.e., analyzing the quality of cylindrical micro-optics. © 2024 by the authors. --//-- This is an open-access article Karitans, V.; Ozolinsh, M.; Fomins, S. Phase Retrieval of One-Dimensional Objects by the Multiple-Plane Gerchberg–Saxton Algorithm Implemented into a Digital Signal Processor. Optics 2024, 5, 514-522. https://doi.org/10.3390/opt5040038 published under the CC BY 4.0 licence.
This research was funded by the University of Latvia Foundation and company MikrtoTik; grant number 2257. Institute of Solid State Physics, University of Latvia as the Center of Excellence has received funding from the European Union's Horizon 2020 Framework Programme H2020-WIDESPREAD-01-2016-2017-TeamingPhase2 under grant agreement No. 739508, project CAMART2.
Keywords: Research Subject Categories::NATURAL SCIENCES::Physics; aberrations; adaptive optics; diffraction; phase retrieval